If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(8) + 4x + 10 = 229 Multiply -9 * 8 -72 + 4x + 10 = 229 Reorder the terms: -72 + 10 + 4x = 229 Combine like terms: -72 + 10 = -62 -62 + 4x = 229 Solving -62 + 4x = 229 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '62' to each side of the equation. -62 + 62 + 4x = 229 + 62 Combine like terms: -62 + 62 = 0 0 + 4x = 229 + 62 4x = 229 + 62 Combine like terms: 229 + 62 = 291 4x = 291 Divide each side by '4'. x = 72.75 Simplifying x = 72.75
| x+76=48+2x+28 | | Sr-2(2r+8)=16 | | 3(4x-1)=8(x+3)+1 | | 3(3c-1)-4=5c+9 | | 16+(-17)= | | y*y-16=9 | | 2(2y-2)-6=-2 | | x(2)+5x+4=0 | | 2(2y-2)-6=2 | | a=19.25-10 | | 4x^2-x+46=0 | | X+y-2z=10 | | .27v-1.6=.32v-2 | | 4x^2-x+56=0 | | 4-5=8+3 | | 41+5y-15=14y-9-2y | | 4x^2-x+56=31 | | 2x+7(2x-13)=37 | | 5(4y-6)-3=22 | | 4lnx^3-3lnx^2=12 | | -4(3n-2)-n=-(n-1) | | -9n+9=-63 | | -70+2x=-5x+77 | | -5-4v=-5+v+2-7v | | Y=-(3-0) | | 2x-2y=63 | | x(5-x).2=-1-4-1 | | 2(4y-3)-3=-3 | | Y=-(3-1) | | 4=-9+6 | | t=sq | | 3a(2a+b)= |